2007
DOI: 10.2133/dmpk.22.41
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of CS-023 (RO4908463), a Novel Parenteral Carbapenem Antibiotic, and Meropenem as Substrates of Human Renal Transporters

Abstract: To characterize the renal handling of CS-023 (RO4908463), a novel parenteral carbapenem antibiotic, and meropenem in humans, we examined their affinities as substrates to human renal transporters. In vitro studies on the uptake of [14C]CS-023 and [14C]meropenem were conducted using HEK293 cells expressing human organic anion transporters (hOAT) 1, hOAT3, hOAT4, and the human organic cation transporters (hOCT) 1 and hOCT2. CS-023 did not serve as the substrate for any of the transporters tested. On the other ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 29 publications
0
22
0
2
Order By: Relevance
“…Body weight and LBM in males are generally greater than in females, as the ratio of body fat to body weight in males is lower than that in females. The logarithm of the partition coefficient (1 -octanol/ water) in meropenem is reported as -3.28 [22], and therefore meropenem seems to be distributed to watersoluble compartments. Considering the physicochemical characteristics of meropenem, LBM in patient might be related to V c and body weight may have an indirect relationship to Vc.…”
Section: Discussionmentioning
confidence: 99%
“…Body weight and LBM in males are generally greater than in females, as the ratio of body fat to body weight in males is lower than that in females. The logarithm of the partition coefficient (1 -octanol/ water) in meropenem is reported as -3.28 [22], and therefore meropenem seems to be distributed to watersoluble compartments. Considering the physicochemical characteristics of meropenem, LBM in patient might be related to V c and body weight may have an indirect relationship to Vc.…”
Section: Discussionmentioning
confidence: 99%
“…6 Shibayama et al reported that the lack of recognition of tomopenem by renal transporters involved in uptake across the basolateral membrane is one of the reasons for its long plasma half-life in humans compared with meropenem, since no tomopenem molecules exist as an anionic form at physiological pH. 20 The MICs of tomopenem for clinical isolates of P. aeruginosa showed more activity than meropenem. 3 Considering the longer half-life of tomopenem, the %T.MIC for tomopenem is much higher than that for meropenem for humans.…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vivo work has shown that tubular secretion in rabbits is not involved in the clearance of tomopenem, in contrast to meropenem (16). In vitro work using cells expressing human organic transporters also supported the idea by showing that tomopenem was not a substrate of these transporters, again in contrast to meropenem (17). The CL R of metabolite in healthy subjects was greater than the glomerular filtration rate.…”
Section: Discussionmentioning
confidence: 92%